A mutation in the Icsbp1 gene causes susceptibility to infection and a chronic myeloid leukemia–like syndrome in BXH-2 mice - Turcotte, Karine (The Rockefeller University Press, 2005)
BXH-2 mice develop a fatal myeloid leukemia by a two-step mutagenic process. First, a BXH-2–specific recessive mutation causes a myeloproliferative syndrome. Second, retroviral insertions alter oncogenes or tumor suppressors, resulting in clonal expansion of leukemic cells. We have identified a recessive locus on chromosome 8 (Myls) that is responsible for myeloproliferation in BXH-2. This Myls interval has been narrowed down to 2 Mb and found to contain several positional candidates, including the interferon consensus sequence–binding protein 1 gene (Icsbp, also known as interferon regulatory factor 8 [IRF8]). We show that BXH-2 mice carry a mutation (915 C to T) resulting in an arginine-to-cysteine substitution at position 294 within the predicted IRF association domain of the protein. Although expression of Icsbp1 mRNA transcripts is normal in BXH-2 splenocytes, these cells are unable to produce interleukin 12 and interferon-γ in response to activating stimuli, confirming that R294C behaves as a loss-of-function mutation. Myeloproliferation in BXH-2 mice is concomitant to increased susceptibility to Mycobacterium bovis (BCG) despite the presence of resistance alleles at the Nramp1 locus. These results suggest a two-step model for chronic myeloid leukemia in BXH-2, in which inactivation of Icsbp1 predisposes to myeloproliferation and immunodeficiency. This event is required for retroviral replication, and subsequent insertional mutagenesis that causes leukemia in BXH-2 mice.